Characterizing a tropical soil via seismic in situ tests - Rocha, Breno Padovezi [UNESP]; Giacheti, Heraldo Luiz [UNESP] (Sociedade Brasileira de Geofisica, 2019)
The shear wave velocity (Vs) is an important geotechnical parameter to be used in dynamic problems (e.g. earthquakes and vibration problems) as well as in static deformation analysis such as excavations and foundation engineering design. There are several in situ seismic tests to determine Vs such as the crosshole and the downhole techniques, as well as hybrid tests (e.g. seismic dilatometer – SDMT). This paper presents crosshole, downhole and SDMT tests carried out in a typical tropical soil profile from Brazil. Advantages and limitations regarding the test procedures and interpretation are briefly presented and differences observed among Vs determined by these techniques are discussed. Shear wave velocities (Vs) estimated from the crosshole, downhole and SDMT tests ranging from 194 to 370 m/s. The shear wave velocity suggests that the experimental site could be divided into two strata, which are in agreement with soil profile description. The maximum shear modulus (G0) calculated from the Vs by theory of elasticity can be used to show the investigated tropical soil is a typical unusual geomaterial. This article also emphasizes that the SDMT is a useful test for site investigation since it allows a great means for profiling geostratigraphy and soil engineering properties during routine site investigation as well as for dynamics problems.
Keywords: Crosshole; Downhole; Maximum shear modulus; SDMT; Shear wave velocity